SOCIAL PROBLEM OF PHYSICAL DEVELOPMENT PUPILS OF RURAL SCHOOLS OF THE REGION - V. Biragov; A. Doeva (Вестник университета)
The article discusses the impact of social factors on physical development students of rural schools in particular Arhonskoy village of North Ossetia-Alania. It was found that adolescents are lagging behind in their physical development of standardized indicators, hence the need to intensify systematic physical exercise. on compulsory school lessons.